(3GdfXQjI GdYGeI ddMUGfI ai bGfhf GdELQGAGJ GdLfGFjI (B/ s - (3QVG NjQi egOi EeGes; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3JYQVfG ai gPg GdQSGdI dHMK ehVhY jYO ef Cge GdehVhYGJ h CNWQgG ai GdELQGAGJ GdLfGFjI CdG h gh (B((3GdMUGfI ai bGfhf GdELQGAGJ GdLfGFjI(B): (3aHMKfG MUGfI QFjS GdOhdI h CYVGA GdHQdeGf h GdbVGI h GdeMGejf(B: (3h Pdc ai GdbGfhf GdeUQi h GdbGfhf GdebGQf(B. (3h JHOh CgejI HMK gPG GdehVhY ai Cf GdMUGfI JYO GSJKfGA ef GdbGfhf GdYGe GdPi jaJQV GdeSGhGI Hjf GdehGWfjf EdG Cf gPG GdGSJKfGA jLO eHQQGJg ai CehQ YOI YQVfGgG Ydi eOGQ GdHMK(B. (3h bO JHjfG Cf gPg GdMUGfI dG JYJHQ GeJjGkRG TNUkjG h EfeG JbQQJ ddgjFI Ch GdSdWI GdJi jfJei EdjgG GdeJeJY HJdc GdMUGfI(B. (3h dG jYfi JbQjQgG Cf GdCaYGd ZjQ GdeTQhYI GdJi jQJcHgG GdeSJajO HJdc GdMUGfI SJUHM CaYGdkG eTQhYI Ch eHGMI(B: (3h dcf cd eG jYfjg Pdc gh EQLGA GJNGP GdELQGAGJ GdLfGFjI h GdbGfhfjI HMb GdeSJajO ef Jdc GdMUGfI(B: (3ShGA CcGf QFjkSG HdOhdI Ch YVkhG aj GdHQdeGf Ch bGVkjG Ch eMGekjG EdG HYO ehGabI GdLgGJ GdeNJUI bGfhkfGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2016s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B627-678s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdMUGfIs; (3GdfXQjI GdYGeIs; (3bGfhf GdELQGAGJ GdLfGFjIs; (3MUGfI CYVGA GdHQdeGf s; (3MUGfI GdeMGej s; (3GdMUGfI GdHQdeGfjI s; (3MUGfI QFjS GdOhdI s; (3GdMUGfI eGfY ef ehGfY GdeSFhdjI s; (3GdMUGfI hehGfY GdYbGH s; (3GdSfO GdbGfhfj ddMUGfI s; (3YdI JbQjQ GdMUGfI GdHQdeGfjI s; (3fWGb MUGfI QFjS GdOhdI s; (3GdfWGb GdecGfj s; (3GdMUGfI GdELQGFjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs